Transcriptome Analysis of Stephania tetrandra and Characterization of Norcoclaurine-6-O-Methyltransferase Involved in Benzylisoquinoline Alkaloid Biosynthesis - Li, Kunlun; Chen, Xuefei; Zhang, Jianbo; Wang, Can; Xu, Qiwei; Hu, Jiangning; Kai, Guoyin; Feng, Yue (Frontiers in Plant Science, 2022)
Stephania tetrandra (S. Moore) is a source of traditional Chinese medicine that is widely used to treat rheumatism, rheumatoid arthritis, edema, and hypertension. Benzylisoquinoline alkaloids (BIAs) are the main bioactive compounds. However, the current understanding of the biosynthesis of BIAs in S. tetrandra is poor. Metabolite and transcriptomic analyses of the stem, leaf, xylem, and epidermis of S. tetrandra were performed to identify candidate genes associated with BIAs biosynthesis. Ac-cording to the metabolite analysis, the majority of the BIAs accumulated in the root, especially in the epidermis. Transcriptome sequencing revealed a total of 113338 unigenes that were generated by de novo assembly. Among them, 79638 unigenes were successfully annotated, and 42 candidate structural genes associated with 15 steps of BIA biosynthesis identified. Additionally, a novel (S)-norcoclaurine-6-O-methyltransferase (6OMT) gene was identified in S. tetrandra, named St6OMT2. Recombinant St6OMT2 catalyzed (S)-norcoclaurine methylation to form (S)-coclaurine in vitro. Maximum activity of St6OMT2 was determined at 30°C and pH 6.0 in NaAc-HAc buffer. Its half-life at 50°C was 22 min with the Km and kcat of 28.2 µM and 1.5s-1, respectively. Our results provide crucial transcriptome information for S. tetrandra, shedding light on the understanding of BIAs biosynthesis and further gene functional characterization.